Localization of Scopolamine Induced Electrocortical Brain Activity Changes, in Healthy Humans at Rest. (6th May 2013) - Ramos Reis, Pedro Miguel; Eckhardt, Holger; Denise, Pierre; Bodem, Friedrich; Lochmann, Matthias
Abstract To prevent the participants of parabolic flights from nausea they are optionally treated with subcutaneously injected antiemetic scopolamine. The range of side effects of this substance include reductions of the α‐2 frequency band. Previous studies, however, have given no information as to which generator centers are responsible for this effect. The objective of this study therefore, is to identify the cortex area that may be responsible for this effect. Six participants were subcutaneously administered 0.7 mg of scopolamine. EEG was recorded for 10 minutes before to 20 minutes after injection. Data preprocessing followed including filtering and artifact minimization. A statistical analysis was performed with sLORETA/eLORETA software for each subject over a time window from 3 minutes before to 17–20 minutes after scopolamine injection. Results show, that in the BA7, the precuneus, on both hemispheres suffered a α‐2 activity decrease in absolute power. The identified brain cortex center is an important hub with high connectivity and centrality values within the neural network. It contributes to the control of movement and to space orientation. Therefore, an activity alteration in this area can possibly explain the antiemetic effect of scopolamine and open a window to understand the origin of motion sickness.